Customers' awareness, attitude and patronage of islamic banking in Nigeria (2015)
This study examines customers’ awareness of Islamic banking products and services in Nigeria and explores their attitude towards them. It also investigates their patronage of the banks. An 18-item questionnaire was designed for businesspersons, Muslims and non-Muslims, to obtain information on issues such as awareness of Islamic banking, loans without interest, collateral security, agency, partnership based on sharing of profits and losses and patronage of an interest free financial system. The results show the willingness of the Muslims and a large number of non-Muslims to patronise Islamic banking products and services. Products and services offered by a large number of the respondents were sharī‘ah-compliant. Their readiness to give collateral security, which is neither compulsory nor against the dictates of Islam, indicates their attitude and preparedness to patronise Islamic banks. However, a few non-Muslim respondents state they will not patronise Islamic banking products even if they are profitable and they are the only products in the banking sector in Nigeria. This study will assist promoters of Islamic banks in Nigeria to know where they can establish full-fledged Islamic banks. There is need for the existing and the potential Islamic banks to create more public awareness on Islamic banks.